Reading Activities at Rumah Langit Foundation as Implications of Indonesian Learning - Aulia Fitriyani; Lia Lianti; Yeni Yeni; Syahna Raulina; Najib Farhan; Irwan Siagia (International Journal of Social Service and Research, 2022)
Reading is an activity that is very beneficial for everyone. Many things can be obtained in life, if someone is diligent in reading. In the world of education, making reading one of the students' habits is a hope for all parents and teaching staff in schools. The development of this reading activity cannot be separated from the great interest of the students to want to do it and the Indonesian language learning which is well managed by the teachers at the school. Reading, which essentially includes the study of the Indonesian language and is used as one of the important teaching materials, is expected to be able to arouse students' interest in reading. Language teachers are expected to be able to help students overcome reading difficulties by teaching good reading techniques and utilizing existing facilities so that reading culture can be realized in schools